ANALYSIS OF SHARIA MARKETING CONSTRAINTS IN INDONESIA - B. Basrowi; Reza Ronaldo (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2019)
The purpose of this study is to theoretically examine the various constraints of sharia marketing in Indonesia in the general sector, banking, and insurance. The method used is a descriptive method by studying literature and realistic phenomena that develop in Indonesia. Data analysis was performed using four stages of descriptive analysis. Based on the results of the study, it can be concluded that the marketing constraints in Indonesia can be classified into two major typologies, namely the constraints of Muslim internal marketing itself (micro) and from the outside (macro). Constraints from within can be overcome by increasing the capacity of all Islamic resources owned. Meanwhile, external constraints are overcome by suggesting to the government, the Ministry of Finance, BI, and the FSA to always increase its support for the Islamic economy in the form of regulations and other support.==============================================================================================Analisis Hambatan Marketing Syariah di Indonesia. Tujuan dari penelitian ini adalah untuk menguji secara teoritis berbagai kendala pemasaran syariah di Indonesia di sektor umum, perbankan dan asuransi. Metode yang digunakan adalah metode deskriptif dengan mempelajari literatur dan fenomena realistis yang berkembang di Indonesia. Analisis data dilakukan dengan menggunakan empat tahap analisis deskriptif. Berdasarkan hasil penelitian, dapat disimpulkan bahwa kendala pemasaran di Indonesia dapat diklasifikasikan menjadi dua tipologi utama, yaitu kendala pemasaran internal Muslim itu sendiri (mikro) dan dari luar (makro). Kendala dari dalam dapat diatasi dengan meningkatkan kapasitas semua sumber daya Islam yang dimiliki. Sementara itu, kendala eksternal diatasi dengan menyarankan kepada pemerintah, Kementerian Keuangan, BI, dan FSA untuk selalu meningkatkan dukungannya bagi ekonomi Islam dalam bentuk regulasi dan dukungan lainnya.